Bakat dan Minat - Ardita Meila Sari; Melisa Kamila; Sawaluddin Sawaluddin; Linda Yarni (Universitas Pahlawan Tuanku Tambusai, 2023)
Talents and interests have an important role in individual development, especially at the early stages of life. This research describes the definition, differences and characteristics of talents and interests and how to develop them. Talent is an innate ability that is potential and needs to be developed through training and education. Meanwhile, interest is an affective tendency towards an activity that develops along with an individual's physical and mental growth. This article discusses the characteristics of gifted children, involving aspects such as intellectual ability, creativity and motivation. Identifying these characteristics helps teachers and parents support the development of gifted children. In addition, types of talents are also discussed, illustrating variations in achievement based on their function and nature. The research method used is a qualitative descriptive method with a focus on literature study. The research results present the definition of talent as above average ability, creativity and responsibility. Meanwhile, interest includes curiosity, affective tendencies, and the desire to pay attention to certain activities. This research also describes the characteristics of gifted children, involving intellectual, creativity and motivation aspects. Types of talents are divided based on their function and nature of achievement, such as psychophysical, psychological, typical and compound talents. How to develop talents and interests includes courage, practice, environmental support, and understanding the obstacles that may be faced. The conclusions of this research highlight the importance of understanding talents and interests in the context of education, career development, and professional choice. Identification of individual talents and interests helps in decision making regarding educational and career paths. With better understanding, we can support individuals' optimal development, help them reach their full potential, and live lives in accordance with their talents and interests.